Micromonospora costi sp. nov., isolated from a leaf of Costus speciosus - Chitti Thawai (My University, 2015)
An endophytic actinobacterial strain, CS1-12(T), was isolated from a leaf of Costus speciosus. Single spores were observed directly on the substrate mycelia. The cell-wall peptidoglycan of this strain exhibited meso-diaminopimelic acid and 3-OH-meso-diaminopimelic acid. Arabinose, glucose, ribose, xylose and rhamnose were detected as whole-cell sugars. The diagnostic phospholipids of this strain were phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol and phosphatidylinositol mannosides. The predominant menaquinones were MK-10(H6), MK-10(H8), MK-9(H4) and MK-10(H4). The main components of the cellular fatty acids (>10%) were iso-C15 : 0, anteiso-C17 : 0, iso-C16 : 0 and anteiso-C15 : 0. The G+C content of the genomic DNA was 72.8 mol%. 16S rRNA gene sequence analysis data showed that strain CS1-12(T) should be classified in the genus Micromonospora and that it is closely related to Micromonospora fulviviridis DSM 43906(T) (99.3%). The physiological, biochemical and chemotaxonomic properties, including the DNA-DNA hybridization results, indicated that strain CS1-12(T) could be judged a novel species of the genus Micromonospora , for which the name Micromonospora costi sp. nov. is proposed. The type strain is CS1-12(T) ( =BCC 58124(T) =NBRC 109518(T)).
Keywords: Micromonospora; Diaminopimelic acid; Arabinose; Strain (injury); Rhamnose; Genomics and Phylogenetic Studies